Analysis of the Impact of Language Acquisition Factors on Listening Skills Using Structural Equation Modeling in Arabic Language Education Students at State Islamic University Raden Intan Lampung - Nur, Muhammad Fahrudin; Zaeni, Rahmania Auriel; Hilmi, Danial (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The selection of language acquisition factors as a research topic is urgent due to the lack of clarity on which factor most significantly supports language competence, particularly in receptive skills like listening in Arabic learning. Understanding this is crucial to assist learners in maximizing their potential. Purpose. This quantitative study, using an explanatory design, investigates the influence of affective, cognitive, and social factors on the improvement of students' listening skills in Arabic. The data was analyzed using Structural Equation Modelling (SEM). Method. The research involved students from the Arabic Language Education Study Program at UIN Raden Intan Lampung. Data were collected via questionnaires measuring the impact of the three factors on listening competence (maharah istima') and analyzed using SEM to assess the relationships between these factors. Results. The results indicate that cognitive factors (e.g., intelligence, talent, and learning styles) have a minimal influence on listening competence. Affective factors (e.g., motivation, personality, and anxiety) have a moderate effect, while social factors, particularly attitude, have the strongest influence on improving listening skills. Conclusion. This study highlights the importance of focusing on social factors to improve listening skills in Arabic learning. Educators can enhance their teaching methods by addressing these key factors, ensuring better student outcomes and more effective language acquisition.